2021
DOI: 10.1097/pcc.0000000000002836
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Self-Harm in Children and Adolescents Admitted to PICUs in the United States

Abstract: To characterize the epidemiology of children and adolescents admitted for deliberate self-harm to PICUs in the United States by examining patient demographics, diagnoses, modes of self-harm, and outcomes.DESIGN: Descriptive analysis of a large, multicenter, quality-controlled database. SETTING:The 137 PICUs participating in the Virtual Pediatric Systems database during the study period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…We found that nearly three-quarters of self-harm admissions involved females and toxic ingestions, which is congruent with the pattern of critical self-harm observed in the preceding decade (9). Admissions for toxic ingestions rarely result in death (9, 25), unlike the high mortality observed in self-harm associated with hanging or firearms (9).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found that nearly three-quarters of self-harm admissions involved females and toxic ingestions, which is congruent with the pattern of critical self-harm observed in the preceding decade (9). Admissions for toxic ingestions rarely result in death (9, 25), unlike the high mortality observed in self-harm associated with hanging or firearms (9).…”
Section: Discussionsupporting
confidence: 84%
“…We found that nearly three-quarters of self-harm admissions involved females and toxic ingestions, which is congruent with the pattern of critical self-harm observed in the preceding decade (9). Admissions for toxic ingestions rarely result in death (9,25), unlike the high mortality observed in self-harm associated with hanging or firearms (9). Therefore, it is unsurprising that the lower number of admissions for hanging and higher number of admissions for toxic ingestions in our study during the pandemic period would have resulted in a lower number of deaths following PICU admission.…”
Section: What This Study Meanssupporting
confidence: 85%
See 1 more Smart Citation
“…For example, during the pandemic, there were 3.9 deaths per 10 000 person-years compared with 28.1 self-harm events per 10 000 person-years. Mortality did not change from before to during the pandemic, because most self-harm events among adolescents and young adults tend to be nonfatal, while the case-fatality rate from COVID-19 in this age group has been very low . The overall large number of cases recorded within a universal health care system enabled us to generate stable and precise risk estimates, including by sociodemographic factors related to intentional injury or mortality …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ingestions among adolescents are a predictor of suicide and premature death (4). Unfortunately, the field of pediatrics has seen a startling trend of increasing hospitalizations for suicidal ideation and suicide attempt, with hospitalizations for these diagnoses tripling in prevalence from 2008 to 2015 (5) and admissions to the PICU for self-harm doubling from 2009 to 2017 (6). These trends in self-harm and suicide attempts in adolescents have only further worsened since the onset of the COVID-19 pandemic (7).…”
mentioning
confidence: 99%